VALUE OF EDUCATION: INVERSION OF MEANINGS - Dmitry A. Sevostyanov; Alisa R. Gainanova (Высшее образование в России)
Higher education in Russia is going through a crisis. This crisis is connected with the lack of ideology in the sphere of education. As a result, the purpose and meaning of education are undergoing inversion. They are not directed at the development of society and its institutions, but at the satisfaction of the needs of discrete education institutions, and also at rendering private educational services. As a result, the society wastes huge resources assigned for education, but the education activities does not reach the effect. This situation requires urgent measures from the state.